Aetiological factors of hoarseness of voice in patients attending in a district level hospital (Bangladesh Journal of Otorhinolaryngology, 2019)
Background: Information about causes or related factors involving voice change was studied mainly in central tertiary level hospitals previously, not in hospital in peripheral districts in BangladeshObjective: To find out and evaluate the etiological factors of hoarseness of voice irrespective of age and sex. Setting: Pabna medical college, a 250 bedded hospital in BangladeshMethods: This was a cross sectional, non- randomized and longitudinal study conducted from 1st august 2011 to July 2017. All the patients with history of hoarseness underwent clinical examination, routine as well as special investigation to find the diagnosis. The final results were analyzed by simple manual analysis with frequency and percentage using SPSS program in 2017. Results: There were total 200 patients included in the study. Among them the age groups of 21 – 30 years and 31 – 40 years were mainly suffer from hoarseness. Similarly, among 200 patients 144 (72%) were males whereas 56 (28%) were females with male to female ratio of 2.5:1. The most common cause as per the distribution was acute laryngitis with frequency of 34% followed by acid peptic laryngitis, 25.5%, neoplasms of larynx 12%, whereas tuberculosis of larynx, intubation granuloma, trauma was very few.Conclusion: There was etiological variation in hoarseness ranging from simple laryngitis to malignancies. So it is important not to ignore the hoarseness and precise history, examination and investigations should be done Bangladesh J of Otorhinolaryngology; October 2018; 24(2): 125-130